Beneish M-Score, Audit Opinions, and Financial Manipulation: Evidence from Indonesia’s Infrastructure Sector - Kurniawan, Umarudin; Ridwansyah, Eksa; Aulia, Siska (Politeknik Negeri Madiun, 2025)
The increasing incidence of financial statement manipulation in Indonesia has raised serious concerns regarding the credibility of audit opinions issued by independent auditors. This study investigates the extent to which audit opinions reflect indications of financial manipulation, utilizing the Beneish M-Score model as a diagnostic tool. The research focuses on infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Employing a descriptive quantitative approach and binary logistic regression analysis, companies are classified as either manipulators or non-manipulators based on their M-Score, and subsequently compared with the audit opinions they received. Findings reveal a sharp rise in the number of companies flagged as manipulators, reaching a peak of 85% in 2022 before declining to 65% in 2023. Alarmingly, most of these identified manipulators still received Unqualified Opinions, highlighting a significant audit expectation gap. This discrepancy suggests potential weaknesses in auditors’ fraud risk assessment and underscores the urgent need for enhanced professional scepticism and analytical rigor in the audit process.